ANALISA PENERAPAN PBL PADA MATA KULIAH PPKN DITINJAU DARI RANAH KOGNITIF - Seri Hartati; Nella Lucky (LPPM Universitas Abdurrab, 2017)
Civil Education is a compulsory course that is held throughout the universities in Indonesia. The discussion in this course is the history of five principles, the understanding of five principles, elements of ethics according to five principles, The Constitution, and the laws relating to five principles and citizenship. The material which given by Lecturer in this subject is by oral presentation, where the lecturer gives a material and followed by a discussion or question and answer. In this study, researchers wanted to apply PBL (problem based learning) in the civil education course. The aim in this research is the researchers can determine the students' understanding of this subject during class is not just rely on the material on the concept of five principles, Citizenship and legislation, but also associated with a problem that is happening and related with this course. The expectations from this research is students can have better cognitive abilities if the discussion of five principles course to be combined with the implementation of PBL compared to oral lecturing course. Key words: five principles, PBL, Lecturer, Student, implementation, cognitive